Involvement of hippocampal acetylcholinergic receptors in electroacupuncture analgesia in neuropathic pain rats - Chen, Shu Ping (Behav Brain Funct, 2016)
BACKGROUND: Cumulating evidence has shown a close correlation between electroacupuncture stimulation (EAS) frequency-specific analgesic effect and central opioid peptides. However, the actions of hippocampal acetylcholinergic receptors have not been determined. This study aims to observe the effect of different frequencies of EAS on the expression of hippocampal muscarinic and nicotinic acetylcholinergic receptors (mAChRs, nAChRs) in neuropathic pain rats for revealing their relationship. METHODS: Forty male Wistar rats were randomly and equally divided into sham, CCI model, 2, 2/15 and 100 HzEA groups. The neuropathic pain model was established by ligature of the left sciatic nerve to induce chronic constriction injury (CCI). EAS was applied to bilateral Zusanli (ST36) and Yanglingquan (GB34) for 30 min, once daily for 14 days except weekends. The mechanical pain thresholds (withdrawal latencies, PWLs) of bilateral hindpaws were measured. The expression levels of hippocampal M1 and M2 mAChR, and α4 and β2 nAChR genes and proteins were detected by quantitative RT-PCR and Western blot, separately. The involvement of mAChR and nAChR in the analgesic effect of EAS was confirmed by intra-hippocampal microinjection of M(1)mAChR antagonist (Pirenzepine) and α4β2 nAChR antagonist (dihydro-beta-erythroidine) respectively. RESULTS: Following EAS, the CCI-induced increase of difference values of bilateral PWLs on day 6 and 14 was significantly reduced (P < 0.05), with 2/15 Hz being greater than 100 Hz EAS on day 14 (P < 0.05). After 2 weeks’ EAS, the decreased expression levels of M1 mAChR mRNA of both 2 and 2/15 Hz groups and M1 mAChR protein of the three EAS groups, α4 AChR mRNA of the 2/15 Hz group and β2 nAChR protein of the three EAS groups were considerably increased (P < 0.05), suggesting an involvement of M1 mAChR and β2 nAChR proteins in EAS-induced pain relief. No significant changes were found in the expression of M2 mAChR mRNA and protein, α4 nAChR protein and β2 nAChR mRNA after CCI and EAS (P > 0.05). The analgesic effect of EAS was abolished by intra-hippocampal microinjection of M(1)mAChR and α4β2 nAChR antagonists respectively. CONCLUSIONS: EAS of ST36-GB34 produces a cumulative analgesic effect in neuropathic pain rats, which is frequency-dependent and probably mediated by hippocampal M1 mAChR and β2 nAChR proteins.